Growth of Listeria monocytogenes in thawed frozen foods - Kataoka, Ai (Kansas State University, 2011)
In February 2008, the FDA released a draft Compliance Policy Guide (CPG) on Listeria monocytogenes and proposed that ready-to-eat (RTE) foods that do not support the growth of L. monocytogenes may contain up to 100 CFU/g of this pathogen. Frozen foods such as ice cream fall in that category since they are consumed in the frozen state. However, other frozen foods, such as vegetables and seafood that are thawed and served at salad and food bars, may support the growth of Listeria and would not be allowed to contain 100 CFU/g according to the draft CPG. In the current study, growth curves were generated for L. monocytogenes inoculated onto four thawed frozen foods - corn, green peas, crabmeat, and shrimp - stored at 4, 8, 12, and 20ºC. Growth parameters, lag phase duration (LPD), and exponential growth rate (EGR) were determined using a two-phase linear growth model and the Square Root Model. The results demonstrated that L. monocytogenes has a very short LPD on these thawed frozen foods during refrigerated storage and that there would be several orders of magnitude of growth (i.e., more than 1.7 log increase at 4 ºC) of the organism before the product is found to be organoleptically unacceptable. Although it would not be possible to take advantage of any extended lag phase duration caused by freeze injury to the organism, frozen foods containing less than 100 CFU/g of L. monocytogenes that are thawed, or thawed and cooked, and then consumed immediately, should not represent a public health hazard.
Keywords: Listeria monocytogenes; Modeling; Frozen food; Ready-to-eat food; Frozen and thawing; Food Science (0359); Microbiology (0410)